Role of miR‐223‐3p in pulmonary arterial hypertension via targeting ITGB3 in the ECM pathway. (3rd December 2018) - Liu, Aijun; Liu, Yifan; Li, Bin; Yang, Ming; Liu, Yang; Su, Junwu
Abstract : Objectives: To investigate the functions of miR‐223‐3p and ITGB3 in pulmonary arterial hypertension (PAH). Materials and Methods: Microarray analysis was used to detect differentially expressed genes and microRNAs. In in vitro models, the expressions of miR‐223‐3p and ITGB3 were detected by qRT‐PCR and Western blot. α‐SMA expression and cell proliferation were analysed by immunofluorescence and MTT assay, respectively. In in vivo models, PAH progressions were determined by measuring the levels of mPAP and RVSP. Lung and myocardial tissues were subjected to HE staining and Masson and Sirius red‐saturated carbazotic acid staining to investigate the pathological features. Results: The microarray analysis revealed that ITGB3 was upregulated, while hsa‐miR‐223‐3p was downregulated in PAH. After the induction of hypoxia, miR‐223‐3p was downregulated and ITGB3 was upregulated in PASMCs. Hypoxia induction promoted cell proliferation and inhibited α‐SMA expression in PASMCs. Both the upregulation of miR‐223‐3p and the downregulation of ITGB3 attenuated the aberrant proliferation induced by hypoxia conditions. After approximately 4 weeks, the mPAP and RVSP levels of rats injected with MCT were decreased by the overexpression of miR‐223‐3p or the silencing of ITGB3 . The staining results revealed that both miR‐223‐3p overexpression and ITGB3 knockdown alleviated the pulmonary vascular remodelling and improved the PAH pathological features of rats. Conclusions: MiR‐223‐3p alleviated the progression of PAH by suppressing the expression of ITGB3, a finding which provides novel targets for clinical treatment.